INTERAKSI ANTARA MAKROFAG DAN JARINGAN ADIPOSA PADA OBESITAS - Wardhana, I Made W.; Wangko, Sunny (UNIVERSITAS SAM RATULANGI, 2011)
Abstract: In adipose tissues of obese people there is an activation of multiple signaling pathways towards hypertrophic adipocytes, associated with infiltration of macrophages.Â These cells trigger inflammatory reactions in those tissues, that attract more macrophages from bone marrows; therefore, increasing the reactions. Moreover, there is a paracrine loop that consists of saturated fatty acids and TNF-Î± derived from macrophages and adipocytes. These two substances create an inflammatory/inflammation cycle, characterized by an up-regulation of pro-inflammatory adipokines and a down-regulation of anti-inflammatory adipokines. Disre-gulation of adipokines production in adipose tissues of obese people in vivo shows that there is a clear/strong interaction between adipocytes and macrophages in causing a chronic inflammation in the tissues. Key words: macrophages, adipose tissue, cytokines.Â Â Abstrak: Pada jaringan adiposa orang obes terjadi aktivasi multiple signaling pathways terhadap adiposit yang hipertrofi, disertai adanya infiltrasi makrofag. Sel-sel ini memicu terjadinya reaksi inflamasi pada jaringan adiposa tersebut, yang selanjutnya menarik makrofag dari sumsum tulang, dengan akibat meningkatnya proses inflamasi. Selain itu terdapat lengkung parakrin yang meliputi asam lemak jenuh dan TNF-Î± yang berasal dari makrofag dan adiposit. Kedua bahan tersebut membentuk suatu siklus inflamasi yang ditandai oleh up-regulation dari adipokin pro-inflamasi dan down-regulation dari adipokin anti-inflamasi. Disregulasi produksi adipokin pada jaringan adiposa orang obes in vivo menunjukkan adanya hubungan erat antara adiposit dan makrofag sebagai mekanisme potensial yang menyebabkan inflamasi kronis pada jaringan adiposa. Kata kunci: makrofag, jaringan adiposa, sitokin.